2013
DOI: 10.1182/blood-2012-05-433045
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression of VEGF by ZNF24: mechanistic studies and vascular consequences in vivo

Abstract: Key Points• ZNF24 represses VEGF transcription through direct binding to an 11-bp fragment of the VEGF proximal promoter.• ZNF24 functions as a negative regulator of developmental and tumor angiogenesis by inhibiting VEGF transcription.VEGF is a key regulator of normal and pathologic angiogenesis. Although many trans-activating factors of VEGF have been described, the transcriptional repression of VEGF remains much less understood. We have previously reported the identification of a SCAN domain-containing C2H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 37 publications
1
48
0
Order By: Relevance
“…In accordance with our results, some studies in humans have shown that serum VEGF levels were higher in patients with breast cancer when compared to healthy subjects and inversely correlated with survival (46,47). On the other hand, Duranyildiz et al (48) and El Tarhouny et al (49) did not observe any significant difference between serum VEGF levels in patients with breast cancer and the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with our results, some studies in humans have shown that serum VEGF levels were higher in patients with breast cancer when compared to healthy subjects and inversely correlated with survival (46,47). On the other hand, Duranyildiz et al (48) and El Tarhouny et al (49) did not observe any significant difference between serum VEGF levels in patients with breast cancer and the control group.…”
Section: Discussionsupporting
confidence: 92%
“…In humans, there was a study that compared the serum levels of HIF-1α in diabetic patients with breast cancer and control groups, demonstrating the HIF-1α levels were markedly higher in the patient group than in the controls (55). Other authors found higher serum HIF-1α levels in patients with lung cancer (57), as well as patients with liver cancer (46).…”
Section: Discussionmentioning
confidence: 99%
“…Our results have demonstrated that ZNF24 serves as a new positive regulator of the angiogenic potential of microvascular ECs. Interestingly, we observed the opposite effect of ZNF24 in human breast cancer cells, in which it functions as a potent inhibitor of tumor angiogenesis by repressing the transcription of VEGF (10, 11). One possible reason for the distinct functions of ZNF24 in different cell types is that similar to many other transcription factors, the function of ZNF24 may be context dependent.…”
Section: Discussionmentioning
confidence: 83%
“…In ECs, ZNF24 regulates the mRNA levels of MMP2, CDKN3 and CCND2. To explore whether MMP2, CDKN3 , and CCND2 are direct target genes for ZNF24 in HMVEC cells, we searched the proximal promoter regions of these genes for known ZNF24 binding sites: TCAT repeats (57), ATTAATT (12), and GCTTTCCATTT (11). There is no known ZNF24 binding site within the proximal promoter regions of these genes, indicating that ZNF24 may regulate the transcription of these genes indirectly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation